Delayed antibiotic prescription in upper respiratory tract infections: a new trend?. (3rd August 2021) - Castanheira, Carolina; Andrade, Isabel; Cruz, Rui
Abstract: Background: Upper respiratory tract infections (URTI) are one of the main reasons for consultation in primary care. Approximately 60% of all antibiotic prescriptions aim at the treatment of URTI, even without a laboratory-based diagnosis. Delayed antibiotic prescription in primary care has shown to reduce antibiotic consumption, without increasing risk of complications, yet is not widely used. Rapid tests to confirm the etiology of URTI are available at pharmacies, but not purchased routinely. In this context, the aim of this study is to assess the knowledge of rapid tests for the diagnosis of URTI, and the awareness of strategies to decrease antibiotic use. Methods: A team of experts in the field developed a questionnaire specifically for the purpose of this study. The Pharmacy graduate students of ESTESC-Coimbra Health School (Portugal) answered the questionnaire online. Results: Over 90% of the respondents with a URTI stated that the general practitioner prescribed the antibiotic without a lab test. When given the option, 58% are willing to pay up to 50 Euros for a rapid test, yet are not familiar with any brand. Although the respondents aren't familiarized with the concept, when asked, the majority (87%) are more likely to choose a delayed than an immediate prescription. Conclusions: Pharmacy graduates are willing to support the use of delayed prescription, to give time for the lab confirmation of the diagnosis. A broader dissemination of the clinical evidence supporting the use of rapid tests and of delayed prescription is necessary to help managing URTI.